Editorial: low population mortality from COVID‐19 in countries south of latitude 35 degrees North—supports vitamin D as a factor determining severity. Authors' reply. Issue 12 (12th May 2020) - Garg, Mayur; Al‐Ani, Aysha; Mitchell, Hannah; Hendy, Philip; Christensen, Britt
Abstract : LINKED CONTENT This article is linked to Al‐Ani et al and Rhodes et al papers. To view these articles, visit https://doi.org/10.1111/apt.15779 and https://doi.org/10.1111/apt.15777 .